2020
DOI: 10.14260/jemds/2020/117
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Levels in Acute Coronary Syndromes Admitted in Medical Intensive Care Unit in a Tertiary Care Hospital

Abstract: BACKGROUND Coronary artery disease (CAD) is the leading cause of mortality in men and women. Acute coronary syndrome (ACS), is a major reason for hospitalisation in our country. Dyslipidemia has been identified as one of the most important modifiable risk factors for CAD. The aim of the study was to determine the prevalence and pattern of dyslipidaemia and its relation to other modifiable risk factors. METHODS 100 cases were studied in a Krishna Institutes of Medical Sciences, Karad, over a period of 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The present research also highlights the significance of lipid profiles in relation to MI risk; heightened total cholesterol, LDL cholesterol, and triglyceride concentrations correlated with an increased likelihood of experiencing STEMI/non-STEMI. These findings are consistent with previous research demonstrating an elevated dyslipidemia prevalence in patients with ACS, regardless of their obesity status [ 41 , 42 ]. These results emphasize the crucial role of lipid management in cardiovascular disease prevention and management.…”
Section: Discussionsupporting
confidence: 93%
“…The present research also highlights the significance of lipid profiles in relation to MI risk; heightened total cholesterol, LDL cholesterol, and triglyceride concentrations correlated with an increased likelihood of experiencing STEMI/non-STEMI. These findings are consistent with previous research demonstrating an elevated dyslipidemia prevalence in patients with ACS, regardless of their obesity status [ 41 , 42 ]. These results emphasize the crucial role of lipid management in cardiovascular disease prevention and management.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, confounding factors were not taken into account. Thirdly, among earlier Indian studies [21][22][23], the Indian Council of Medical Research-India Diabetes (ICMR-INDIAB) Study [24] also reported low levels of high-density lipoprotein (HDL). Hence, we did not aim to study this lipoprotein parameter.…”
Section: Study Limitationsmentioning
confidence: 99%